2014
DOI: 10.1155/2014/125810
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Region Dimensions in Children: A CT Study and Clinical Implications

Abstract: Atresias of nasal cavity, especially in young children, pose an essential problem in children's otolaryngology. Only a few morphometric studies of nasal cavity concerning healthy neonates and young infants without nasal stenosis are available. Multislice computed tomography is a perfect tool enabling a precise evaluation of anatomic structures. The aim of this study was a complex morphometric evaluation of clinically important bone and mucosal structures of nasal cavity and examination of their dependence on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 32 publications
2
26
0
1
Order By: Relevance
“…For nasopharynx vertical dimension (NVD) we have noted an average positive correlation of r xy = 0.351, statistically significant. Our previous study confirmed the correlation between nasal cavity dimensions and child's age, yet that correlation was of different strength [7]. In connection with the above, assessment has been made of mutual dependencies between the analysed structures, and the strength of those dependencies has been assessed, taking into account the location of measured dimensions within the nasal cavity and nasopharynx.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…For nasopharynx vertical dimension (NVD) we have noted an average positive correlation of r xy = 0.351, statistically significant. Our previous study confirmed the correlation between nasal cavity dimensions and child's age, yet that correlation was of different strength [7]. In connection with the above, assessment has been made of mutual dependencies between the analysed structures, and the strength of those dependencies has been assessed, taking into account the location of measured dimensions within the nasal cavity and nasopharynx.…”
Section: Resultssupporting
confidence: 75%
“…Studies by various authors demonstrated that the width of posterior nares itself increases with age by an accurately defined value. This has been confirmed by our earlier studies, in which we demonstrated that this dimension increases at the rate of 0.162 mm/week [7]. Slovis et al [14] assessed the change in posterior nares dimension in a group of neonates, children and young adults, from their day of birth until the age of 20.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…The study conducted by Djupesland and Lyholm (32) indicated that the size of the nose and the airspace in the nasal aperture did not depend upon the sex. Likus et al (33) reported the absence of statistically significant differences between the sexes, as regards the values and relations of all nasal parameters measured. The disagreement between findings could be explained by the differences in the age of the studied samples.…”
Section: Discussionmentioning
confidence: 95%
“…Likus et al. reported the absence of statistically significant differences between the sexes, as regards the values and relations of all nasal parameters measured. The disagreement between findings could be explained by the differences in the age of the studied samples.…”
Section: Discussionmentioning
confidence: 96%